A dry-mixed mortar and its preparation method and application

By using cellulose ether and starch ether of different viscosity in dry-mixed mortar and adding components such as redispersible latex powder, polypropylene fiber and slag powder, the problem of poor water retention and ease in cement mortar plastering technology is solved. , achieving efficient crack resistance and compressive strength improvement, reducing construction costs and material waste.

CN116477905BActive Publication Date: 2024-12-13GUANGZHOU PANYU POLYTECHNIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310481052.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2024-12-13
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

The existing cement mortar plastering technology has problems such as poor water retention and ease, wasteful ash falling, large, low strength, hollow delamination and cracking are difficult to control.

Method used

Two cellulose ethers of different viscosity are combined with starch ether, combined with redispersible latex powder, polypropylene fiber, slag powder and silicon fume, and the water retention, viscosity, crack resistance and flow of the mortar are improved through ultrasonic premix. , enhance the compactness and compressive strength of the mortar.

Benefits of technology

It significantly improves the water retention, easiness, crack resistance and compressive strength of the mortar, reduces floor ash, extends opening time, reduces costs, and improves construction efficiency and economic benefits of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to a dry-mixed mortar and a preparation method and application thereof, belonging to the technical field of premixed mortar. The dry-mixed mortar of the present invention comprises the following components in parts by weight: 200-300 parts of cementitious material, 1-2 parts of cellulose ether A, 0.3-0.8 parts of cellulose ether B, 0.3-0.5 parts of starch ether, and the aggregate is supplemented to a total weight of 1000 parts; the viscosity of the cellulose ether A at 25°C is 30000-40000 mPa·s; the viscosity of the cellulose ether B at 25°C is 100000-120000 mPa·s. The present invention obtains a dry-mixed mortar with good water retention, fluidity, cohesiveness and crack resistance by combining specific slag powder, silica fume, cellulose ether, starch ether, redispersible latex powder and polypropylene fiber with cementitious material and aggregate. The dry-mixed mortar is applied in building decoration, has low requirements on the wetness of the wall, and can overcome the shortcomings of ordinary mortar such as easy slurry bursting and large shrinkage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of premixed mortar, and in particular to a dry-mixed mortar and a preparation method and application thereof. Background Art

[0002] With the acceleration of the modernization of cities in my country, premixed dry mortar is attracting attention due to its irreplaceable advantages, and will eventually replace traditional on-site mixed mortar and become the ideal material for the new generation of high-quality buildings. However, with the passage of time and the improvement of people's housing requirements, the existing cement mortar plastering technology has exposed many problems, such as poor water retention and workability, large waste of dust, low strength, and hollowing, delamination and cracking are difficult to control. Therefore, a special thin-layer plastering mortar is specially designed to meet the needs of market development. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a dry-mixed mortar with high water retention and good cohesiveness, and a preparation method and application thereof.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] In a first aspect, the present invention provides a dry-mixed mortar, comprising the following components in parts by weight: 200-300 parts of a cementitious material, 1-2 parts of a cellulose ether A, 0.3-0.8 parts of a cellulose ether B, 0.3-0.5 parts of a starch ether, and an aggregate to a total weight of 1000 parts; the cellulose ether A has a viscosity of 30000-40000 mPa·s at 25°C; the cellulose ether B has a viscosity of 100000-120000 mPa·s at 25°C.

[0006] The present invention selects two cellulose ethers with different viscosities to match with starch ether, and the obtained dry-mixed mortar has the advantages of high water retention and good cohesion. Cellulose ether is a polymer compound that can be used in various fields. During the experiment, the inventor found that the viscosity of cellulose ether has a certain influence on the fluidity, water retention and cohesion of the mortar. When cellulose ether with a viscosity of 40000mPa·s and cellulose ether with a viscosity of 100000mPa·s are added to the dry-mixed mortar, it can play a role in thickening and water retention, and at the same time has good crack resistance, a long open time, and can make the material homogeneous. The existing dry-mixed mortar has the problems of poor water retention and workability, and low bonding strength. Although a single cellulose ether is added as an auxiliary material to the dry-mixed mortar, the water retention of the mortar can be improved, the bonding strength, fluidity and crack resistance are reduced. The present invention adopts a combination of two cellulose ethers with different viscosities and then matches them with starch ether, which can effectively improve the water retention and workability of the mortar, and can also improve the fluidity, crack resistance, sag resistance and open time of the mortar, can reduce dust on the floor, improve the strength and stability of the mortar and reduce costs, with high economic benefits.

[0007] As a preferred embodiment of the dry-mixed mortar of the present invention, the viscosity of the cellulose ether A is 40000 mPa·s at 25°C; the viscosity of the cellulose ether B is 100000 mPa·s at 25°C; the purity of the cellulose ether A is ≥99.5%, and the purity of the cellulose ether B is ≥99.5%. In addition to viscosity, the present invention also found that the purity of cellulose ether is closely related to the shrinkage rate and open time of the dry-mixed mortar. When the purity of the cellulose ether is 96% and the viscosity is 100000 mPa·s, the 28d shrinkage rate of the prepared dry-mixed mortar is only 0.12, and the open time is 20min. Compared with the dry-mixed mortar of the present invention, the shrinkage rate is increased by 10 times and the open time is shortened by 1 time. The increase in the shrinkage rate of the mortar easily leads to a decrease in the cohesiveness of the plaster mortar and causes cracking, which does not meet the requirement of good cohesiveness of the dry-mixed mortar of the present invention.

[0008] As a preferred embodiment of the dry-mixed mortar of the present invention, the dry-mixed mortar further comprises 3-10 parts by weight of redispersible latex powder, 0.5-1 parts by weight of polypropylene fiber, 50-100 parts by weight of slag powder, and 10-30 parts by weight of silica fume. Adding slag powder to the dry-mixed mortar of the present invention can effectively improve the compactness and strength of the mortar. When combined with silica fume, the aggregate, filler, cementitious material, etc. in the mortar can have a particle size distribution in the state of particle diameter, and the material is more compact; adding redispersible latex powder can significantly improve the bonding performance of the mortar, while reducing the brittleness of the mortar and improving the flexibility of the mortar. When combined with polypropylene fiber, it can synergistically enhance the crack resistance of the mortar.

[0009] As a preferred embodiment of the dry-mixed mortar of the present invention, the redispersible latex powder is a redispersible latex powder of an acrylic system. The addition of the redispersible latex powder of an acrylic system to the dry-mixed mortar of the present invention can significantly improve the bonding performance of the mortar, while reducing the brittleness of the mortar, improving the flexibility, greatly improving the anti-shrinkage effect of the mortar, and improving the crack resistance.

[0010] As a preferred embodiment of the dry-mixed mortar of the present invention, the length of the polypropylene fiber is 3 mm. The polypropylene fiber preferably has a length of 3 mm, which can further improve the anti-shrinkage effect of the mortar and improve the crack resistance when combined with the redispersible latex powder of the acrylic system.

[0011] As a preferred embodiment of the dry-mixed mortar of the present invention, the particle size of the slag powder is not greater than 13 μm; the activity index of the silica fume is greater than 105%. The present invention preferably uses slag powder with a maximum particle size of 13 μm and silica fume with an activity index greater than 105%, so that the various components in the mortar are mixed more evenly and the material is more dense. The obtained mortar has an anti-seepage pressure greater than 1.5 MPa and a compressive strength greater than 82 MPa, which is far superior to ordinary mortar.

[0012] As a preferred embodiment of the dry-mixed mortar of the present invention, the aggregate includes quartz sand of 40-70 mesh and quartz sand of 60-120 mesh; the quartz sand of 40-70 mesh accounts for 40-60% of the total weight of the aggregate, and the quartz sand of 60-120 mesh accounts for 40-60% of the total weight of the aggregate. The present invention preferably uses two different sizes of quartz sand as aggregate, which can improve the gradation between different components and make the mortar more dense.

[0013] In a second aspect, the present invention provides a method for preparing the above-mentioned dry-mixed mortar, which comprises the following steps:

[0014] Premixing starch ether, part of aggregate and part of gelling material in an ultrasonic mixing device to obtain a mixed system; the part of aggregate accounts for 20-40% of the total weight of aggregate, and the gelling material accounts for 20-40% of the total weight of gelling material;

[0015] The mixed system, the remaining parts by weight of aggregate, the remaining parts by weight of cementitious material, cellulose ether A and cellulose ether B are mixed to obtain a dry-mixed mortar.

[0016] As a preferred embodiment of the method for preparing the dry-mixed mortar of the present invention, the dry-mixed mortar further comprises redispersible latex powder, polypropylene fiber, slag powder and silica fume, and the steps of preparing the dry-mixed mortar are as follows:

[0017] (1) premixing slag powder, silica fume, starch ether, polypropylene fiber, part of aggregate and part of cementitious material in an ultrasonic mixing device to obtain a mixed system; the part of aggregate accounts for 20-40% by weight of the total aggregate, and the cementitious material accounts for 20-40% by weight of the total cementitious material;

[0018] (2) The mixed system, the remaining parts by weight of aggregate, the remaining parts by weight of cementitious material, cellulose ether and redispersible latex powder are mixed to obtain a dry-mixed mortar.

[0019] In a third aspect, the present invention provides application of the above-mentioned dry-mixed mortar in building plaster mortar.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention combines specific cellulose ethers and starch ethers with gelling materials and aggregates to obtain dry-mixed mortar with good water retention, cohesiveness, crack resistance and sag resistance. When used in building decoration, the dry-mixed mortar of the present invention has low requirements on the wetness of the wall and can overcome the shortcomings of ordinary mortar such as easy slurry bursting and large shrinkage; the plaster layer has a small thickness and a short curing time, which reduces the amount of mortar used and reduces the construction time.

[0022] (2) The dry-mixed mortar of the present invention improves the bonding performance and flexibility of the mortar, reduces brittleness, and significantly improves the crack resistance of the mortar by adding redispersible latex powder and polypropylene fiber; by adding slag powder and silica fume, the aggregate, filler, cementitious material, etc. in the mortar have a particle grading in the state of particle size, the material is denser, and has excellent anti-seepage and anti-compression properties.

[0023] (3) The dry-mixed mortar of the present invention has the required strength, tensile resistance and flexibility through the combination of various components. The tensile stress can resist the chemical shrinkage stress of the hardened mortar itself and a certain external force, thereby preventing the plaster layer from cracking and increasing the open time of the mortar, which can make the mortar more stable and have higher compressive strength in practical applications.

[0024] (4) The dry-mixed mortar of the present invention uses ultrasound to pre-mix powder components with smaller particle sizes, thereby improving the uniformity of the dry-mixed mortar while reducing the mixing and production time, thereby improving production efficiency. DETAILED DESCRIPTION

[0025] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0026] In the following examples and comparative examples, the slag powder A is produced by Shaoguan Iron and Steel, with a grade of S95 and a particle size of no more than 13 μm;

[0027] The manufacturer of slag powder B is Kaiju, the brand is S95, and the particle size is 1-10mm.

[0028] The manufacturer of cellulose ether A1 is Hercules-Temper, the brand is 30011C, the viscosity is 40000mPa·s at 25°C, and the purity is 99.5%;

[0029] The manufacturer of cellulose ether B1 is Heda, the brand is MK100000s, the viscosity is 100000 mPa·s at 25°C, and the purity is 99.5%;

[0030] The manufacturer of cellulose ether A2 is Meixin, the brand is MH-3017, the viscosity is 30000mPa·s at 25℃, and the purity is 99.5%;

[0031] The manufacturer of cellulose ether B2 is Ashland, the brand is Benecel K250 PH PRM, the viscosity is 120000 mPa·s at 25°C, and the purity is 99.5%;

[0032] The manufacturer of cellulose ether C is Zhucheng, the brand is C8618, the viscosity is 100000 mPa·s at 25°C, and the purity is 96%;

[0033] Redispersible latex powder A is an acrylic acid system redispersible latex powder, manufactured by Wacker, with a brand number of 5010N;

[0034] Redispersible latex powder B is ethylene / vinyl acetate system Del redispersible latex powder, the manufacturer is Baochen, the brand is 6035E;

[0035] The polypropylene fiber manufacturer is Anfeng, and the length is 3mm;

[0036] The silica fume manufacturer is Dechang Weiye, the brand is DC-C18, and the activity index is >105%;

[0037] The cementitious material is P·II type Portland cement, which is commercially available;

[0038] The remaining materials and reagents, unless otherwise specified, can be obtained from commercial sources.

[0039] Examples 1 to 3 and Comparative Examples 1 to 4

[0040] The components of the dry-mixed mortars of Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Table 1. The cementitious material used in the Examples and Comparative Examples is Type II Portland cement.

[0041] The preparation method of the dry-mixed mortar of Examples 1 to 3 and Comparative Examples 1 to 4 is as follows:

[0042] (1) premixing slag powder, silica fume, starch ether, polypropylene fiber, 100 parts by weight of aggregate and 100 parts by weight of type II Portland cement in an ultrasonic mixing device to obtain a mixed system;

[0043] (2) The mixed system, the remaining parts by weight of aggregate, the remaining parts by weight of type II silicate cement, cellulose ether and redispersible latex powder are mixed to obtain a dry-mixed mortar.

[0044] Table 1 Composition of dry-mixed mortars of Examples 1 to 3 and Comparative Examples 1 to 4 (by weight)

[0045]

[0046] Example 5

[0047] The preparation method of the dry-mixed mortar in Example 5 is the same as that in Example 1, and the composition components are similar to those in Example 1, except that cellulose ether A1 is replaced by cellulose ether A2, and cellulose ether B1 is replaced by cellulose ether B2.

[0048] Comparative Example 4

[0049] The preparation method of the dry-mixed mortar in Comparative Example 4 is the same as that in Example 1, and the composition components are similar to those in Example 1, except that the redispersible latex powder A of the acrylic system is replaced by the redispersible latex powder B of the ethylene / vinyl acetate system.

[0050] Comparative Example 5

[0051] The preparation method of the dry-mixed mortar in Comparative Example 5 is the same as that in Example 1, and the composition components are similar to those in Example 1, except that the slag powder A with a particle size not greater than 13 μm is replaced by slag powder B with a particle size not greater than 10 mm.

[0052] Effect example performance test

[0053] The dry-mixed mortars of Examples 1 to 5 and Comparative Examples 1 to 5 were respectively added with water accounting for 26% of the total weight of the dry-mixed mortar to prepare mortars for performance testing. The test results are shown in Table 2. The test items are as follows:

[0054] The compressive strength, 28-day shrinkage, water retention and consistency are tested according to the test standard of dry-mixed interface mortar (DIT) or dry-mixed plaster mortar (DP) in GB / T 25181-2019 "Premixed Mortar";

[0055] Shear bond strength and tensile bond strength (untreated) are tested according to the test standards in JC / T 907-2018 "Concrete Interface Treatment Agent".

[0056] Table 2 Performance test results of dry-mixed mortar of Examples 1 to 5 and Comparative Examples 1 to 5

[0057]

[0058] As shown in Table 1, the dry-mixed mortar of the present invention has excellent compressive strength, shear bond strength and tensile bond strength, extremely small shrinkage and high water retention, which indicates that the dry-mixed mortar of the present invention has good water retention, fluidity and cohesion, good tensile resistance and flexibility, and is a dry-mixed mortar with excellent comprehensive performance.

[0059] The dry-mixed mortar of Example 4 is relatively poor in various indicators compared with those of other examples, which indicates that adding slag powder, silica fume redispersible latex powder and polypropylene fiber to the dry-mixed mortar of the present application can significantly improve various properties of the dry-mixed mortar.

[0060] Compared with Comparative Example 1, the dry-mixed mortar of Example 1 is excellent in compressive strength, shear bond strength and tensile bond strength, with extremely small shrinkage, high water retention and low consistency, indicating that the amount of each component must be within an appropriate range to make the dry-mixed mortar have good water retention, fluidity, cohesion, tensile resistance and flexibility, and obtain a dry-mixed mortar with excellent comprehensive performance.

[0061] Compared with Example 2, the dry-mixed mortar of Example 2 has poor shear bonding strength and shrinkage rate, and low water retention, indicating that the dry-mixed mortar prepared by only selecting cellulose ether with a viscosity of 100000 mPa·s and a purity of 96% has poor water retention and fluidity, which is easy to cause mortar bursting. The poor shrinkage rate causes the mortar to shrink greatly, crack easily, and have a short open time. Therefore, a combination of two cellulose ethers with viscosities of 40000 mPa·s and 100000 mPa·s and a purity of ≥99.5% can enhance the water retention rate of the dry-mixed mortar and improve the crack resistance of the mortar.

[0062] Compared with Example 3, the compressive strength of the dry-mixed mortar in Example 3 is lower, which indicates that the combination of two cellulose ethers with viscosities of 40000 mPa·s and 100000 mPa·s and purity ≥99.5% and starch ether can enhance the compressive strength of the dry-mixed mortar. In addition, the addition of starch ether also improves the anti-sagging performance of the mortar (visually observed from the actual test results on site) and improves the overall performance of the mortar.

[0063] Compared with Example 4, the bonding strength of the dry-mixed mortar in Example 4 decreases. The reason for the decrease in the strength of the mortar is that the ethylene / vinyl acetate system redispersible latex powder is prone to water resistance. Therefore, the use of an acrylic acid system redispersible latex powder can enhance the bonding effect.

[0064] Compared with Example 5, the actual activity performance of the cementitious material of the dry-mixed mortar in Example 5 decreases, resulting in a significant decrease in the general strength of the mortar, and a significant decrease in the compressive strength, bonding strength, etc. Therefore, the use of ultrafine mineral powder with a diameter can enhance the effect of enhancing the hydration strength of the material.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A dry-mix mortar, characterized in that: The invention comprises the following components in parts by weight: 280 parts of gelling material, 1.5 parts of cellulose ether A, 0.7 parts of cellulose ether B, 0.5 parts of starch ether, and 534.9 parts of aggregate; The viscosity of the cellulose ether A at 25°C is 40000 mPa·s; the viscosity of the cellulose ether B at 25°C is 100000 mPa·s; the purity of the cellulose ether A is ≥99.5%, and the purity of the cellulose ether B is ≥99.5%; The dry-mixed mortar further comprises 7 parts by weight of redispersible latex powder, 0.5 parts by weight of polypropylene fiber, 80 parts by weight of slag powder, and 25 parts by weight of silica fume; The redispersible latex powder is a redispersible latex powder of an acrylic acid system; The length of the polypropylene fiber is 3 mm; The particle size of the slag powder is not greater than 13 μm; the activity index of the silica fume is greater than 105%.

2. The dry-mix mortar according to claim 1, characterized in that: The aggregate comprises quartz sand of 40-70 meshes and quartz sand of 70-120 meshes; the quartz sand of 40-70 meshes accounts for 40-60% of the total weight of the aggregate, and the quartz sand of 70-120 meshes accounts for 40-60% of the total weight of the aggregate.

3. The method for preparing the dry-mix mortar according to claim 1, characterized in that: The following steps are involved: Premixing starch ether, part of aggregate and part of gelling material in an ultrasonic mixing device to obtain a mixed system; the part of aggregate accounts for 20-40% of the total weight of aggregate, and the part of gelling material accounts for 20-40% of the total weight of gelling material; The mixed system, the remaining parts by weight of aggregate, the remaining parts by weight of cementitious material, cellulose ether A and cellulose ether B are mixed to obtain a dry-mixed mortar.

4. The method for preparing dry-mixed mortar according to claim 3, characterized in that: The dry-mixed mortar further comprises redispersible latex powder, polypropylene fiber, slag powder and silica fume. The preparation method of the dry-mixed mortar comprises the following steps: (1) premixing slag powder, silica fume, starch ether, polypropylene fiber, part of aggregate and part of cementitious material in an ultrasonic mixing device to obtain a mixed system; the part of aggregate accounts for 20-40% of the total weight of aggregate, and the part of cementitious material accounts for 20-40% of the total weight of cementitious material; (2) The mixed system, the remaining parts by weight of aggregate, the remaining parts by weight of cementitious material, cellulose ether and redispersible latex powder are mixed to obtain a dry-mixed mortar.

5. Application of the dry-mixed mortar as claimed in any one of claims 1 to 2 in building plastering mortar.